2022
DOI: 10.3390/molecules27144366
|View full text |Cite
|
Sign up to set email alerts
|

Novel C60 Fullerenol-Gentamicin Conjugate–Physicochemical Characterization and Evaluation of Antibacterial and Cytotoxic Properties

Abstract: This study aimed to develop, characterize, and evaluate antibacterial and cytotoxic properties of novel fullerene derivative composed of C60 fullerenol and standard aminoglycoside antibiotic–gentamicin (C60 fullerenol-gentamicin conjugate). The successful introduction of gentamicin to fullerenol was confirmed by X-ray photoelectron spectroscopy which together with thermogravimetric and spectroscopic analysis revealing the formula of the composition as C60(OH)12(GLYMO)11(Gentamicin)0.8. The dynamic light scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…[ 37,38,77–81 ] When the concentration of Ful reached 0.25 mg mL −1 , it was discovered that it increased the viability of MC3T3‐E1 cells over 24 h, as shown in Figure 7A. Literature also emphasizes that Ful is a highly biocompatible material, [ 37,38,77–81 ] and previous assessments with Ful concentrations up to 10 mg mL −1 were shown to be noncytotoxic using human skin fibroblasts, [ 77,78 ] murine macrophage cells, [ 80 ] and human epidermal keratinocytes. [ 79 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 37,38,77–81 ] When the concentration of Ful reached 0.25 mg mL −1 , it was discovered that it increased the viability of MC3T3‐E1 cells over 24 h, as shown in Figure 7A. Literature also emphasizes that Ful is a highly biocompatible material, [ 37,38,77–81 ] and previous assessments with Ful concentrations up to 10 mg mL −1 were shown to be noncytotoxic using human skin fibroblasts, [ 77,78 ] murine macrophage cells, [ 80 ] and human epidermal keratinocytes. [ 79 ]…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of well know antibiotic gentamicin was improved by FRL as a carrier for local administration at the wound site Nurzynksa et al 74 Overall impression of the presented works provided a clear conclusion that most of the positive outcomes (organprotection) were related to the antioxidative properties of FRLs. However, in dose-dependent studies with FRL, its cytostatic effect may be much stronger than its antioxidative ability.…”
Section: Antioxidant Antimicrobialmentioning
confidence: 85%
“…Therefore, future investigations should focus on diseases in which oxidative stress might be one of the key causes or consequences. The past 2 decades have confirmed the potential use of FRL in some CNS diseases, 54,55,68,72 infections, 57,65,73,74 ophthalmology, 63 dermatology, 66,69 respiratory, 58 gynecology, 59 osteoporosis, 60,71 alcoholism, 62 thrombosis, 64 and diabetes. 67 Several studies have focused on the central nervous system (CNS), where the antioxidative properties of FRL may have a positive influence on patients with depression, 54 Alzheimer's disease, 55,72 and brain stroke.…”
Section: Potential Medical Use Of Frlmentioning
confidence: 92%
See 1 more Smart Citation
“…In another article, the antibacterial and cytotoxic properties of a novel fullerene derivative composed of C 60 fullerenol and standard aminoglycoside antibiotic–gentamicin (C 60 fullerenol–gentamicin conjugate) were evaluated [ 8 ]. In vitro assays suggested that the developed C 60 fullerenol–gentamicin conjugate possessed the same antibacterial activity as standard gentamicin against various bacterial strains.…”
mentioning
confidence: 99%